Analisis SNA dalam Interaksi Netizen pada Iklan “Oke Gas Prabowo Gibran Paling Pas” - Muhammad Fadillah Abbyyu; Alma Mandjusri; Yoedo shambodo; Resman Muharul Tambunan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study analyzes netizen interactions using Social Network Analysis (SNA) in the comment section of the political advertisement “Oke Gas Prabowo Gibran Paling Pas” on Richard Jersey’s YouTube channel. This study aims to understand how communication structures are formed in digital networks and identify key actors who play a role in spreading political opinions. The approach used is quantitative with a positivist paradigm and descriptive-exploratory analysis techniques. The analyzed data includes nodes (actors), edges (relationships between actors), and network metrics such as diameter, density, reciprocity, centralization, and modularity. The results show that netizen interactions form a complex communication network with a high level of connectivity. Key actors are identified through degree centrality and betweenness centrality, indicating their significant role in information distribution. Additionally, dominant groups function as interaction hubs, while bridging actors facilitate information dissemination between communities. These findings suggest that political communication on social media is influenced not only by the advertisement content itself but also by the network structure surrounding it. Thus, this study contributes to the understanding of how public opinion is formed and spread in digital spaces and its implications for political campaign strategies in the era of social media.